Mortgage risks, debt literacy and financial advice - van Ooijen, Raun; van Rooij, Maarten C.J. (Journal of Banking & Finance, 2016)
A limited understanding of mortgage contracts and the risks involved may have contributed to the outbreak of the 2007–2008 financial crisis. We developed a special questionnaire relating mortgage loan decisions to financial knowledge and financial advice. Our results demonstrate that homeowners appear to be well aware of mortgage risks. Large loans relative to home value are perceived as riskier, as are loans with large mortgage payments relative to income and loans linked to investment vehicles. Homeowners with riskier mortgages indicated that they could encounter financial problems should house prices or their income decline. Homeowners with relatively low debt literacy are more likely to take out traditional mortgages with principal repayments over the maturity of the loan. Riskier mortgages are more prevalent among homeowners with a better understanding of loan contracts. Financially less sophisticated homeowners consulting mortgage brokers, too, hold riskier mortgages.